Plataforma logística de producción en investigación de biocombustible etanol - alveolo pulmonar suburbano occidental Calle 80 (2019)
A logistic model based on a production ring where farmers work in the field, towards two main nuclei that establish a new way for the production of crops without chemical intervention, so that the manufacture of biofuels eradicates the obtaining of fossil fuels , fulfilling the main objective of the master plan and its succession with the partial plan. The bioclimatic approach is given by the channel and the fitotectura, with which renewable energy is generated by means of the tidal energy (given by the channel that is articulated to the project), additionally a systems of catch clouds in the main façade of the project turns the fog in water, the reason is to be so close to the savannah the temperatures vary giving possibility to these instruments of sustainability that will serve to supply the toilets of the building, the c02 produced by the plant and the production of ethanol is solved with the covers , different layers of fabrics filter this component making it not harmful to the environment, said fabrics in polyethylene help to reduce this effect in parallel with the management of fitotectura we managed to catch the rest reducing this carbon dioxide.